Fibronectin within Sodium Alginate Microcapsules Improved Osteogenic Differentiation of BMMSCs in Dose Dependent Manner by Targeting SP7, OCN, CDK1, ZBTB16, and Twist1 Expression - Karim Shamsasenjan; Younes Beygi Khosrowshahi; Mahsa Mahmoodi; Parvin Akbarzadehlaleh; Nesrin Gareayaghi; Babak Nejati (Tabriz University of Medical Sciences, 2022)
Introduction: Insoluble fibronectin as an extracellular matrix (ECM) protein has the potential to promote proliferation, differentiation, and migration of mesenchymal stem cells (MSCs). However, there is limited information about the effects of fibronectin various concentrations on bone marrow-derived MSCs (BMMSCs) function and differentiation. Materials and Methods: In this experimental study, using a gel injection device, BMMSCs were encapsulated in sodium alginate microcapsules containing 1.25% alginate, 1% gelatin, and four different concentrations of fibronectin (0.01, 0.05, 0.1, and 0.2 µg/ml). MTT assay was used to examine the proliferation of BMMSCs in des. Also, BMMSCs apoptosis rates were calculated using Annexin-V/PI staining and FACS analysis within 48 hours of exposure. Alkaline phosphatase (ALP) test was conducted to assess BMMSCs osteogenic differentiation. Finally, mRNA expression levels of the SP7, osteocalcin (OCN), Twist Family BHLH Transcription Factor 1 (Twist1), Peroxisome proliferator‐activated receptor γ2 (PPARγ2), Cyclin-dependent kinase 1 (CDK1), and Zinc Finger And BTB Domain Containing 16 (ZBTB16), which involved in MSCs differentiation process were evaluated using Real-Time PCR following exposure with fibronectin 0.1 µg/ml. Result: According to results, fibronectin had the potential to promote proliferation rates of the BMMSCs, in particular at 0.1 and 0.2 µg/ml concentrations. On the other hand, we showed that various concentrations of the fibronectin were not able to modify apoptosis rates of the BMMSCs, negatively or positively. Notable potential of the fibronectin, to trigger osteogenic differentiation of the BMMSCs was documented. Also, RT-PCR results indicated that fibronectin could augment osteogenic differentiation of cultured BMMSCs Conclusion: Results showed that fibronectin can improve proliferation and osteogenic differentiation of BMMSCs without any effect on these cells' survival.